A preliminary trial of botulinum toxin type A in patients with vestibular migraine: A longitudinal fMRI study - Oh, Sun-Young; Kang, Jin-Ju; Kim, Sohui; Lee, Jong-Min; Kim, Ji-Soo; Dieterich, Marianne (Frontiers in Neurology, 2022)
Objective This study aims to investigate the efficacy of botulinum toxin type A (BTX-A) in the prophylactic management of vestibular migraine (VM) and to determine whether this treatment modulates intrinsic functional brain network. Methods Vestibular migraine patients (n = 20, mean age 45.4 years) who were resistant to conventional prophylactic therapies had BTX-A injection and rs-fMRI before and 2 months after the injection. We also measured the changes in the frequency of vertigo and migraine attacks, symptomatic functional disability scores, and neuropsychiatric inventories. Results After BTX-A injection, the mean monthly frequencies of migraine and vertigo episodes decreased significantly compared with the baseline (p < 0.01, paired t-test). The Headache Impact Test-6 score and the Migraine Disability Assessment, and the vertigo parameters, measured by the Dizziness Handicap Inventory and the Vertigo Symptom Scale, showed an improvement, as did the anxiety and depression scores 2 months after BTX-A treatment. The low-frequency fluctuation analysis of the rs-fMRI data found significant changes in the functional connectivity of the right superior temporal gyrus. Adoption of this cluster as the seed region increased the functional connectivity with the left post-central gyrus, right supramarginal gyrus, and right middle temporal gyrus after BTX-A treatment. Conclusion This prospective study suggests that BTX-A treatment is effective at ameliorating migraine and vertigo symptoms in VM patients who were resistant to conventional therapies. Along with symptomatic improvements, changes in the functional connectivity within the multisensory vestibular and pain networks suggest a dysmodulation of multimodal sensory integration and abnormal cortical processing of the vestibular and pain signals in VM patients.